2010
DOI: 10.2514/1.44650
|View full text |Cite
|
Sign up to set email alerts
|

Current Methods Modeling and Simulating Icing Effects on Aircraft Performance, Stability, Control

Abstract: Icing alters the shape and surface characteristics of aircraft components, which results in altered aerodynamic forces and moments caused by air flow over those iced components. The typical effects of icing are increased drag, reduced stall angle of attack, and reduced maximum lift. In addition to the performance changes, icing can also affect control surface effectiveness, hinge moments, and damping. These effects result in altered aircraft stability and control and flying qualities. Over the past 80 years, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 14 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Characteristics. The change rules of aerodynamic parameters and stability derivatives and nonlinear and stall conditions after icing were studied [15][16][17]. The dynamic response characteristics under different ice severity and distribution conditions [18,19] and icing influence on the overall performance, maneuverability and stability of the aircraft [20] were explored.…”
Section: (2) Effect Of Icing On Aerodynamic and Flight Mechanicsmentioning
confidence: 99%
“…Characteristics. The change rules of aerodynamic parameters and stability derivatives and nonlinear and stall conditions after icing were studied [15][16][17]. The dynamic response characteristics under different ice severity and distribution conditions [18,19] and icing influence on the overall performance, maneuverability and stability of the aircraft [20] were explored.…”
Section: (2) Effect Of Icing On Aerodynamic and Flight Mechanicsmentioning
confidence: 99%
“…Ice accretion over surfaces affects many different industrial fields, such as aeronautics [1], maritime [2], aero-generators [3], power lines [4], etc., causing reduction in efficiency, energy consumption due to the required measures to mitigate it, and most significantly important, safety risks.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 90 years, techniques gradually increasing understanding of icing and improving fidelity of models of icing effects on performance, stability and control have been developed [2]. At the beginning, focus has been on wind tunnel studies of 2-dimensional subscale airfoils [3]- [6] and separate wings [2], [4], [7]. Further researches has been performed to investigate the integrated effects of icing on the aircraft performance, stability and control [2], [4], [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Delta-model was used to simulate various icing effects of a business jet [12]. An analysis of the icing influence on the aerodynamics of transport aircrafts is payed attention in [7], [9], [13]. A very comprehensive review of the past studies on aircraft icing can be found in [14].…”
Section: Introductionmentioning
confidence: 99%